Long-term trends and health impact of PM2.5 and O3 in Tehran, Iran, 2006–2015. (May 2018) - Faridi, Sasan; Shamsipour, Mansour; Krzyzanowski, Michal; Künzli, Nino; Amini, Heresh; Azimi, Faramarz; Malkawi, Mazen; Momeniha, Fatemeh; Gholampour, Akbar; Hassanvand, Mohammad Sadegh; Naddafi, Kazem
Abstract: The main objectives of this study were (1) investigation of the temporal variations of ambient fine particulate matter (PM2.5 ) and ground level ozone (O3 ) concentrations in Tehran megacity, the capital and most populous city in Iran, over a 10-year period from 2006 to 2015, and (2) estimation of their long-term health effects including all-cause and cause-specific mortality. For the first goal, the data of PM2.5 and O3 concentrations, measured at 21 regulatory monitoring network stations in Tehran, were obtained and the temporal trends were investigated. The health impact assessment of PM2.5 and O3 was performed using the World Health Organization (WHO) AirQ+ software updated in 2016 by WHO European Centre for Environment and Health. Local baseline incidences in Tehran level were used to better reveal the health effects associated with PM2.5 and O3 . Our study showed that over 2006–2015, annual mean concentrations of PM2.5 and O3 varied from 24.7 to 38.8 μg m −3 and 35.4 to 76.0 μg m −3, respectively, and were significantly declining in the recent 6 years (2010–2015) for PM2.5 and 8 years (2008–2015) for O3 . However, Tehran citizens were exposed to concentrations of annual PM2.5 exceeding the WHO air quality guideline (WHO AQG) (10 μg m −3 ), U.S. EPA and Iranian standard levels (12 μg m −3 ) during entire study period. We estimated that long-term exposure to ambient PM2.5 contributed to between 24.5% and 36.2% of mortality from cerebrovascular disease (stroke), 19.8% and 24.1% from ischemic heart disease (IHD), 13.6% and 19.2% from lung cancer (LC), 10.7% and 15.3% from chronic obstructive pulmonary disease (COPD), 15.0% and 25.2% from acute lower respiratory infection (ALRI), and 7.6% and 11.3% from all-cause annual mortality in the time period. We further estimated that deaths from IHD accounted for most of mortality attributable to long-term exposure to PM2.5 . The years of life lost (YLL) attributable to PM2.5 was estimated to vary from 67, 970 to 106, 706 during the study period. In addition, long-term exposure to O3 was estimated to be responsible for 0.9% to 2.3% of mortality from respiratory diseases. Overall, long-term exposure to ambient PM2.5 and O3 contributed substantially to mortality in Tehran megacity. Air pollution is a modifiable risk factor. Appropriate sustainable control policies are recommended to protect public health. Graphical abstract: Highlights: Long-term trends and health impacts of PM2.5 and O3 in Tehran were evaluated from 2006–2015. Tehran citizens were exposed to annual PM2.5 approximately 2 to 4 times higher than the WHO guideline level at all times. Annual mean O3 concentrations declined significantly over the whole period study. In 2015, approximately 3800 deaths (> 10 per day) were attributable to long-term exposure to ambient PM2.5 in Tehran.